Assessment Of The Internal Environment Of Gachsaran\'s Shahid Rajai Hospital Using Weisbord Organizational Diagnosis Model - Esmaeel Masoudian; Jamil Sadeghifar; Yusef Masoudian; Moslem Salehi; Mojgan Amiriyan Zadeh; Meysam Mousavi (Tehran University of Medical Sciences, 2013)
Background and Aim: Hospital internal evaluation is considered as one of the most important steps in strategic planning. Therefore, besides the recognition of the weaknesses and limitations of the organization, especially affecting issues on the performance, the responsibility of the organization will be defined. This study was performed for the assessment of internal environment of the Gachsaran's Shahid Rajai Hospital based on Weisbord Organizational Diagnosis model. Materials and Methods: In a cross-sectional study, 123 hospital staff were selected using random sampling formula. Data was collected using Weisbord Questionnaire which consisted of 35 questions in seven areas. Data analysis was conducted using SPSS statistical software and the t-test. Results: Among six variables studied, variable communication with 3/15 ± 1/25 mean and standard deviation has the best situation and reward mechanism with the mean and standard deviation of 4/59 ± 1/32 was the worst. There was a meaningful difference among all variables except for the leadership variable. Conclusion: Based on the findings of this study, Gachsaran's Shahid Rajai hospital has strength in the fields of goals, organizational structure, coordination, and internal organizational communication